Pengabdian Kepada Masyarakat melalui Kegiatan Bakti Sosial Pembagian Sembako dalam rangka Dies Natalis STIE Bima ke-23 - Nur Khusnul Hamidah; Ismunandar Ismunandar; Muhajirin Muhajirin; Amirulmukminin Amirulmukminin; Juwani Juwani (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2025)
Social service is a form of Community Service, aimed at helping others in a cooperative manner without expecting an imbalance of services. This social service is carried out by Lecturers, students and academics of Stie Bima. This activity is very beneficial for both students, lecturers and academics of Stie Bima in fostering a social spirit and concern. Community service activities in the form of sharing basic necessities are to increase togetherness, respect the preservation of nature, revive humanitarian values, build brotherhood. Assistance to those in need is very much needed to be able to help each other. The strong help the weak, those who live well help those who live in need. The methods used include planning, preparation of basic food packages, and implementation of activities carried out on February 14, 2025 with a gathering point on the Stie Bima campus. The results of the purpose of distributing basic necessities that we provide to underprivileged residents can help their economy so that they are able to maintain their lives, and the benefits can be felt by the community around RT / 6 RW / 2 Sarae sub-district.